Regional economic integration in West Africa - Seck, Diery (Advances in African economic, social and political development., 2014)
This book presents a number of key studies pertaining to the most pressing challenges of economic regional integration in West Africa. The issues of monetary coordination, foreign exchange volatility, taxation, savings and macroeconomic convergence are investigated from a regional perspective. The characteristics of West Africas trade policy are reviewed and assessed in comparison to those of the Southern African Development Community (SADC). The extent to which regional integration can tackle the challenge of unemployment is the focus of studies on labour markets. Development of the private sector and coordination of regional cross-border transportation are examined through the lens of economic collaboration between Arab and African countries. The book provides fresh new answers to persistent development questions and sheds new light on long-held views that are either incomplete or no longer true. It also opens new perspectives on the search for sustainable avenues for Africas development. In this regard, it may contribute to the emergence of a new paradigm on Africas development process and its science-based, policy-oriented implementation.